Improvement of Mechanical Properties of Injection-Molded Polylactic Acid–Kenaf Fiber Biocomposite - Anuar, Hazleen; Ahmad, Zuraida; Kovacs, J. G.; Tabi, T. (Sage Publications, 2012)

(untitled)
The motive of this study is to lessen the dependence on non-degradable plastic packaging by developing alternative material; reinforced poly(lactic acid) (PLA) with kenaf fiber (KF) biocomposite using available plastic processing machineries. For that reason, this study focuses on fabrication of PLA–KF biocomposite using intermeshing co-rotating twin-screw extruder and then injection molded for mechanical characterization. The effect of KF loading from 0 to 20 wt% was studied. No coupling agent was added due to high affinity of PLA and KF and both components are hydrophilic in nature. The average of KF aspect ratio is 30. Tensile properties and flexural properties show similar trend where significant improvement was attained at 20 wt% KF content. Scanning electron micrograph of tensile fracture specimen has revealed the hypothesis of interaction between fiber and matrix which subsequently amplified the tensile properties. It is an interesting finding where the experimental value of tensile modulus was 15% higher than theoretical tensile modulus at 20 wt% KF. Additionally, PLA–KF bicomposite produced, has high specific strength and specific modulus. This could suggest that KF may be incorporated into PLA to reduce mass of the end product and substantially reduce the cost of raw materials. As expected, impact strength however decreases with KF content.